Socialna sprejetost nadarjenih učencev in učencev z dodatno strokovno pomočjo v osnovni šoli - Horvat, Marina (Psihološka obzorja (Ljubljana), 2013)
Studies of peer relations in school settings are typically conducted on normative samples of pupils. Less is known about subgroups of pupils with some exceptionalities who may be more vulnerable to developing peer problems in school and are subsequently at risk for later maladjustment. The purpose of present study was therefore to examine social acceptance of gifted pupils and pupils with additional professional help in 6th and 8th-grade of regular elementary school. 194 pupils (50.5% girls) from 12 classes participated in the study; 16 of them (8.3%) were pupils with additional professional help (APH), 39 gifted pupils (20.1%) and one gifted pupil with APH. A composite positive and negative nomination sociometric procedure was employed. Most of the pupils with APH were in rejected and average sociometric group. Pupils with APH received the lowest number of positive and reciprocal nominations and the highest number of negative nominations. Compared to gifted pupils they were less accepted, although no difference in acceptance was found compared to the non-APH pupils. Results showed no significant differences in acceptance of pupils with APH in regard to grade level or gender. Gifted children received the highest number of positive and reciprocal and the lowest number of negative nominations. They were more likely to be average and popular, although no differences in acceptance was found compared to non-gifted pupils. Results suggest the importance of investigating subgroups of pupils with APH in future research.
Keywords: social acceptance; socialna sprejetost; gifted students; nadarjeni učenci; dodatna strokovna pomoč; students with additional professional help; sociometric groups; sociometrične skupine; sociometrija; sociometry